Formulation and Evaluation of New Dosage Form of Calcium and Vitamin D - Sharma, Satish Kumar; Singh, Anand; Bhandari, Anil; Singh, Sudhir (Asian Journal of Pharmaceutical Research and Development, 2020)
The aim of the research work was to develop a new dosage form (tablet in tablet) of calcium and vitamin D. In this research work vitamin D3 was used as vitamin D. This type of dosage form is very useful for elder people and children who have a week swallowing reflex. They have difficulty in swallowing tablets with water. In the present research work, pre-formulated and evaluated chewable tablets of calcium and vitamin D3 (from Formulation and Evaluation of Chewable Tablets of Calcium and Vitamin D) were taken and then moulded into a jelly like material under specified conditions of temperature and humidity and a new dosage form was developed which is sweet, flavored and chewable dosage form (tablet in tablet). The new dosage form was subjected to various tests for evaluation of the new dosage form.